The Woman’s Status in Al-Twariq Societies in The Light of TheHistorical Materialist (Albayan Scientific Journal, 2023)
This paper aims to explain the status of woman in Al-Twariq societies through a specific point of view which is the historical materialist theory. This theory connects the dominant mode of production and its relation with the developmental level of the production forces and its role in the emergence of social formation including the cultural heritage. Also it aims to answer the main research paper question which is there any relation between the dominant mode of production including its relations in Al-Twariq societies and the woman’s status there? The current study revealed that since these societies are considered as desert environments don’t contain any agricultural production pattern which guarantees a kind of stability or maybe because there are other production means that are controlled by man the matter that gives him a kind of more spatial stability and enhances his power there which in turns increases the woman’s physical strength in these societies and guarantees for her a feeling of economic independence that is separated from the man giving her an effective role to participate in all the cultural and social community’s activities.